Exploring the Use of Helminthophagous Fungi in the Control of Helminthoses in Horses: A Review - do Carmo, Tábata Alves; Fonseca, Júlia dos Santos; Braga, Fabio Ribeiro; Paz-Silva, Adolfo; de Soutello, Ricardo Velludo Gomes [UNESP]; de Araújo, Jackson Victor (MDPI, 2025)
With the increase in parasite resistance to anthelmintics in horses, it is becoming essential to look for new approaches to helminth control. Helminths not only cause health problems in horses but also generate economic losses. One promising solution is the use of helminthophagous fungi, which act on the larvae and eggs of parasites. These fungi can be incorporated into horse feed, helping to reduce infestations on pasture. This review explores the potential of these fungi as an effective and sustainable tool for controlling worms in horses, promoting animal health and environmental protection.
Keywords: biological control; chlamydospores; equine; nematodes; nematophagous fungi